2011
DOI: 10.3324/haematol.2011.051557
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of fludarabine sensitivity by all-trans-retinoic acid in chronic lymphocytic leukemia cells

Abstract: BackgroundA subset of patients with fludarabine-resistant chronic lymphocytic leukemia has previously been shown to express elevated intracellular levels of the concentrative high-affinity fludarabine transporter hCNT3, without any detectable related activity. We have recently shown that all-trans-retinoic acid is capable of inducing hCNT3 trafficking to plasma membrane in the MEC1 cell line. We, therefore, evaluated the effect of all-trans-retinoic acid on hCNT3 in primary chronic lymphocytic leukemia cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…In this sense, we have shown that hCNT3 trafficking to the plasma membrane can be induced in the CLL‐derived cell line MEC1, by all‐trans retinoic acid through a TGF‐β1‐mediated mechanism that requires ERK 1/2 and RhoA activation and cytoskeleton integrity (13). This effect can also be reproduced in primary CLL cells in cases of poor ex vivo response to fludarabine treatment (31).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this sense, we have shown that hCNT3 trafficking to the plasma membrane can be induced in the CLL‐derived cell line MEC1, by all‐trans retinoic acid through a TGF‐β1‐mediated mechanism that requires ERK 1/2 and RhoA activation and cytoskeleton integrity (13). This effect can also be reproduced in primary CLL cells in cases of poor ex vivo response to fludarabine treatment (31).…”
Section: Discussionmentioning
confidence: 98%
“…In absorptive epithelia, apical localization of hCNT3 is crucial to determining the vectorial flux of many antiviral and anticancer nucleosides tested so far (5), thus being a major candidate for modulating drug bioavailability and pharmacokinetics. However, in some pathologic conditions such as cancer, hCNTs seem to be down‐regulated (2931). In this regard, it has been reported that low plasma membrane expression of hCNT3 may be related to the poor response to treatment of chronic lymphocytic leukemia (CLL) cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacology [5] and lung cancer [6] as auxiliary medication. Retinoic acid participates in renal development [7,8], and dietary deficiency during pregnancy leads to less number of nephrons at birth [9].…”
Section: Fundamental and Clinicalmentioning
confidence: 99%
“…Many substances have been studied to try to find an appropriate therapeutic tool for preventing or treating kidney pathologies. Among them, the retinoids have been proposed as possible candidates in the literature: retinoids have proved to be useful in human leukemia and lung cancer as auxiliary medication. Retinoic acid participates in renal development , and dietary deficiency during pregnancy leads to less number of nephrons at birth .…”
Section: Introductionmentioning
confidence: 99%
“…Late-stage B-CLL is frequently treated with several different regiments including chemotherapeutic combinations composed of [i] fludarabine and Rituximab (FR); [ii] fludarabine and cyclophosphamide (FC); [iii] fludarabine, cyclophosphamide, and Rituximab (FCR); and [iv] cyclophosphamide, doxorubicin, vincristine and prednisolone (CHOP). The combination of fludarabine and all-trans retinoic acid has enhanced levels of effectiveness against B-CLL [7] as does fludarabine with alkylating agents (cyclophosphamide) which promotes higher response rates and longer progression-free survival.…”
Section: Introductionmentioning
confidence: 99%